2203. Risk Factors for Hepatitis C in Western Africa: An Observational Study in a STI Clinic. (26th November 2018) - Akyar, Eda; Mora, Nallely; Luke, Amy; Layden, Jennifer; Phillips, Richard; Agyarko-Poku, Thomas; Owusu, Dorcas; A-Siaw, Helena; Nahass, Ronald
Abstract: Background: The pattern of hepatitis C virus (HCV) transmission routes in sub-Saharan Africa (SSA) has not been previously well characterized. A recent meta-analysis reported a general population HCV prevalence of 5.4% and HIV co-infection prevalence of 3.6% in SSA, with considerable regional variation. Methods: A cross-sectional study was performed in Kumasi, Ghana. Subjects were recruited from patients attending an STI clinic at a government-supported health center. Subjects completed a survey emphasizing known risk factors for HCV, including sexual behaviors, to capture potential routes of exposure. Surveys were administered in Twi, the local language, with the assistance of trained interpreters. Blood samples were collected and tested for HCV antibodies using DiaSpot Anti-HCV Rapid Screen Tests (USA). Data were analyzed using univariate analysis and logistic regression using SAS 9.4. Results: Of the total 312 subjects, 15 were HCV positive (prevalence 4.8%). The HIV-HCV co-infection prevalence was 5.5%. After adjusting for age and sex, statistically significant associated risk factors for HCV infection ( P < 0.05) include no/low level of education vs. tertiary (OR 5.0), northern region of birth vs. central region (OR 7.3), and traditional body scarring (OR 4.1). Rough sexual practices, ie dry sex, sores, were also explored and were associated with HCV infection ( P = 0.02). Post-hoc stratified analysis of HIV-infected individuals ( n = 201) was performed to identify risk factors among those with HCV co-infection. Significant risk factors ( P < 0.05) in this sub-population include northern region of origin (OR 12.4) and traditional scars or marks (OR 4.6). Conclusion: Two risk factors for HCV infection, ie region of birth and traditional scarring, were significant in both the total clinic population and HIV co-infected individuals suggesting cultural practices are contributing to an increased risk of infection. Among HCV positive individuals, rough sexual practices were significant risk factors; whereas, IV-drug abuse was not. While HCV treatment exists, it is not currently available in West Africa; therefore, it is critical to identify risk factors to best target education programs and screening of populations to limit disease spread. Disclosures: All authors: No reported disclosures.